Caffeine fatalities - Do sales restrictions prevent intentional intoxications? - Thelander, Gunilla; Jönsson, Anna Kristina; Personne, Mark; Forsberg, Gunilla Sjölin; Lundqvist, Kristina Magnusson; Ahlner, Johan (Clinical toxicology (Philadelphia, Pa.), 2010)
Objective. Caffeine is widely available in beverages and in different over-the-counter products, including tablets containing 100 mg caffeine. Because intentional fatal intoxications with caffeine occur, the maximum quantity of caffeine tablets that can be bought over the counter in a single purchase was restricted from 250 to 30 in Sweden in the year 2004. The objective of this article was to study the effect of this decision on the number of fatal caffeine intoxications. Method. In Sweden 95% of all cases undergoing forensic autopsy are screened for a number of drugs including caffeine. All cases during January 1993-September 2009 with a caffeine concentration above 80 μg g blood were recorded. Results. During the study period toxicological investigations were performed in 83,580 forensic autopsies. Caffeine contributed to the fatal outcome in 20 cases (0.02%). Thirteen (65%) of these fatalities occurred before the introduction of the sales restriction. However, no fatal intoxications where caffeine contributed to the cause of death was recorded between May 2007 and September 2009. Conclusion. Overdoses of tablets containing caffeine can be fatal, suicides as well as accidents occur. Restricting the maximum quantity of caffeine tablets available over the counter seemed to be effective in preventing suicides because of caffeine although some time elapsed until the effect was noted. Further monitoring is required to ensure that the observed lower caffeine mortality is a sustained effect.